2012
DOI: 10.1007/s00271-012-0376-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of site-specific irrigation management on grapevine yield and fruit quality attributes

Abstract: Spatial variation in yield and fruit composition has been observed in many vineyards leading to low productivity. In this study, site-specific irrigation was applied in a 6.4 ha commercial vineyard (Vitis vinifera L. cv. Shiraz) block in the Sunraysia region of Australia to improve production in low yielding areas of the block and decrease differences in yield and quality between zones. The block was divided into three irrigation management zones based on normalised difference vegetation index (NDVI). Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Regulated deficit irrigation treatment and PD treatment were imposed across three seasons (Table , Figure ) and compared to the Control, which was the industry standard for the winegrape‐growing region (Alexander and Potter , Pink , Toll et al , McClymont et al ). Differences in seasonal ambient temperature were observed (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Regulated deficit irrigation treatment and PD treatment were imposed across three seasons (Table , Figure ) and compared to the Control, which was the industry standard for the winegrape‐growing region (Alexander and Potter , Pink , Toll et al , McClymont et al ). Differences in seasonal ambient temperature were observed (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…to apply in the field [35]. At present, there are several irrigation technologies for conservation irrigation, such as sprinkler, drip, and other micro-irrigation systems but limited site-specific studies have been done [30,[36][37][38]. For example, a study of the variable-rate drip irrigation system on vineyard found up to 17% increase in yield and a 20% decrease in water consumption compared to uniform irrigation [39].…”
Section: Variable-rate Irrigation Technologiesmentioning
confidence: 99%
“…So, to adapt the vineyard management to environmental variability it is necessary to find strategies that will sustain vineyard productivity and wine quality. The complexity of this scenario calls for diagnostic tools that are more powerful than the simple analysis and interpretation of a limited set of variables . In this regard, here we evaluated the effects of canopy management strategies on grapevine water status during the berry ripening period and on nitrogen in must, wine composition and quality profile.…”
Section: Introductionmentioning
confidence: 99%